2017
DOI: 10.5194/os-2017-82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rising bubbles as mechanism for scavenging and aerosolization of diatoms

Abstract: Abstract. Bubbles rising in clean saline water cause steady displacement of ions at the bubble boundaries that separate anions and cations based on ion mass. Anions of greater mass are resistant to displacement and concentrate on the bubble upper half sphere, while smaller and less massive cations are displaced towards lower pressure of the bottom half sphere. The separation into anionic and cationic domains on the bubble curvatures creates electric polarity that may draw particulates dispersed in the water. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In addition, these organisms are lighter than e.g. diatoms, for which due to having heavy cell walls saturated with silica, wind speed will be of great importance [64]. As can be seen in this study, the amount of diatoms was relatively small.…”
Section: Plos Onementioning
confidence: 51%
“…In addition, these organisms are lighter than e.g. diatoms, for which due to having heavy cell walls saturated with silica, wind speed will be of great importance [64]. As can be seen in this study, the amount of diatoms was relatively small.…”
Section: Plos Onementioning
confidence: 51%
“…Rising bubbles in a water column can pick up particles in a process known as bubble scavenging [8][9][10][11][12]. Other works have already found that the microplastic concentration at the water surface is enriched [36][37][38], yet the mechanism for this enrichment is not identified.…”
Section: Resultsmentioning
confidence: 99%
“…3). Numerous studies have highlighted the relationship between wind strength and sea spray production (Blanchard, 1963;Schlichting, 1974;Monahan et al, 1983;Callaghan et al, 2008;Löndahl, 2014;Tesson et al, 2016;Wiśniewska et al, 2019;Marks et al, 2019). Stronger winds have been shown to enhance the production of sea spray aerosols, in-cluding microalgae, which implies an increased transfer of diatoms from the sea surface microlayer into the atmosphere (Marks et al, 2019).…”
Section: Temporal Variability Of the Diatom Recordmentioning
confidence: 99%
“…Numerous studies have highlighted the relationship between wind strength and sea spray production (Blanchard, 1963;Schlichting, 1974;Monahan et al, 1983;Callaghan et al, 2008;Löndahl, 2014;Tesson et al, 2016;Wiśniewska et al, 2019;Marks et al, 2019). Stronger winds have been shown to enhance the production of sea spray aerosols, in-cluding microalgae, which implies an increased transfer of diatoms from the sea surface microlayer into the atmosphere (Marks et al, 2019). Studies on regional atmospheric circulation confirm that air masses from these regions are effectively transported to ice core sites Abram et al, 2010;Thomas and Bracegirdle, 2015;Allen et al, 2020), therefore establishing an efficient transport pathway from the identified source regions to the ice core sites.…”
Section: Temporal Variability Of the Diatom Recordmentioning
confidence: 99%
See 1 more Smart Citation